NILAI-NILAI PENDIDIKAN ANAK DALAM SISTEM PENDIDIKAN ISLAM MASA DINASTI NASHRID DAN KESULTANAN RUM: SEBUAH KAJIAN HISTORIS-KOMPARATIF - Chandra Maulana (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study aims to analyze the values of child education embedded in the Islamic educational systems of the Nasrid Dynasty in Granada and the Sultanate of Rum in Anatolia through a historical-comparative approach. The research employed a library research method by examining primary and secondary sources related to educational institutions, scholarly traditions, educational figures, and educational values developed within both dynasties. Data analysis was conducted through the stages of heuristics, source criticism, interpretation, and historiography, followed by comparative analysis to identify similarities and differences in educational values relevant to child education. The findings reveal that the Nasrid Dynasty promoted educational values such as literacy culture, love of knowledge, strengthening religious identity, and preservation of intellectual traditions through madrasas, libraries, and scholarly assemblies. Meanwhile, the Sultanate of Rum emphasized holistic educational values through the integration of religious and rational sciences, character building, spiritual development, tolerance, and humanitarian values reflected in Sufi educational traditions and the teachings of Jalal al-Din Rumi. The comparative analysis indicates that both dynasties viewed education as a means of character formation and intellectual development for younger generations, although they differed in educational orientation. The educational values identified in this study remain relevant to contemporary child education, particularly in strengthening literacy, character education, spiritual intelligence, and holistic learning. Therefore, the educational heritage of the Nasrid Dynasty and the Sultanate of Rum can serve as an important source of inspiration for developing sustainable and character-based child education.